A simple procedure for determining the mode I bridging stress of composite DCB laminates without measuring the crack opening displacement. (1st July 2020) - Gong, Yu; Chen, Xinjian; Tao, Junan; Zhao, Libin; Zhang, Jianyu; Hu, Ning
Abstract: Fiber bridging usually presents in the wake of crack tip in delamination tests of composite double cantilever beam (DCB) specimens. An effective method determining the bridging law is required, which can be applied for developing accurate prediction model. However, extracting the bridging law in the fiber bridging zone is difficult. Here, a simple procedure is proposed for the determination of mode I bridging law. The crack opening displacement (COD) at the initial pre-crack tip is obtained by a numerical method based on the experimental R -curve from standard DCB tests. The bridging laws can then be determined via the J -integral method, which are compared with experimental ones and good agreements exist between each other. Moreover, the obtained bridging law is employed in a three-linear cohesive zone model, which is applied in cohesive elements for predicting the delamination growth behavior in DCB specimens. The responses are well-described by the three-linear cohesive zone model using the obtained bridging law, illustrating the applicability of the proposed procedure for determining bridging law. This new procedure provides a simple way to obtain the bridging law without the measurement of the COD. It is a step towards a better understanding of delamination mechanism in laminated composites.